The issues of using PISA in school geography classes - Hamrayeva Gulhayo (Proceedings of The ICECRS, 2019)
This article about the importance of working pisa tests with geographic lessons for learning geography is determined by the fact that without a new pedagogic technology can not be realized the main feature of any geography, object and phenomenon, namely geographic.In addition to, this article about what is the PISA program.